Music in Churches: Nourishing Your Congregation's Musical Life - Clark, Linda J. (Rowman & Littlefield Publishers, 1994)
Clergy, worship or music committees, organists, and choir or music directors will find this a practical and invaluable guide to the role and power of music to express and form faith. Clark researched twenty-four Episcopal and United Methodist congregations to discover how churchgoers express their faith through music. Discover how music can either enhance or detract from tradition and faith experience. Explore how it can shape your congregation's character.